Development of the SOPANSPEAK Interactive Multimedia Application as a Learning Innovation to Instill Language Politeness in Early Childhood - Khusniyah, Syarifatul; Santoso, Sandy Tegariyani Putri; Mukhlis, Akhmad; Rochmah, Ainur (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2026)
Language politeness is an important aspect in the moral, social, and communication development of early childhood. However, language politeness learning in early childhood education institutions is generally still carried out through habituation and direct examples, so that children do not receive interactive and contextual learning experiences. This study aims to develop an interactive multimedia application, SOPANSPEAK, as a learning medium to instill language politeness in early childhood. The study used the Research and Development (R&D) method with the Lee & Owens model, which includes the stages of analysis, design, development, implementation, and evaluation. The study was conducted at TK Muslimat NU 2 Singosari with research subjects of 15 children in group B3 aged 5–6 years. Data collection techniques included observation, interviews, validation by material experts, validation by media experts, and product trials. The resulting product is an interactive multimedia application that integrates digital stories, educational songs, learning videos, educational games, interactive puzzles, and reward features in one learning medium. The results showed that the SOPANSPEAK application met the eligibility criteria based on expert assessment and user trials. This application can be used as a learning innovation to help children understand and get used to using polite language in everyday life.